The Effectiveness of English Teacher Education Practice - Indah Sari (Budapest International Research and Critics University, 2021)
This study aimed to describe about the effectiveness of English teacher education practice in Medan. This study applied the descriptive qualitative design. The subjects of this study were 10 mentors and 30 participants of English teacher education practice. Furthermore, the questionnaire was administered in order to collect the data. The data analysis used the data condensation, data display and verification. The English teacher education practice in Medan was quite effective since most of respondents gave the “good” statement for socializing and coordinating of the program, coordinating the program preparation, and coordination of monitoring and evaluation of English teacher education practice. Meanwhile, most of them gave the “fair” statement for the obstacles during the program implementation preparation and the effort to overcome the problems by the related institution in the English teacher education practice. The result of the study proved that the English teacher education practice in Medan fulfilled the classification or indicators of the effectiveness in implementing the education practice for English teacher.